Work Improvement At A Car Manufacturing Company - Mat Saman, Muhamad Zameri; Law, Cheak Ying (Penerbit UTM Press, 2002)
Productivity has been identified as an important role in any organization, especially for manufacturing sectors to gain more profit that leads to prosperity [1]. This paper reports a work improvement project in a car manufacturing company. It involves problem identification at the metal finish line and proposing recommendation to improve the current situation more efficiently. Based on the observation and data online work-in-progress (WIP) has been identified as a major problem and this is caused by the insufficient movements due to material handlings and unbalanced workload. Method improvement technique is used to determine the best method of carrying out a task in order to eliminate the unnecessary movements. Then, line-balancing technique is used to minimize the idle time at every station or the percentage of line balance loss (LBL). In order to verify the results that were obtained from the generated line-balancing alternative, Witness simulation package is used to obtain the output. One effective alternative is chosen based on the results obtained from the simulation and cost justification. Then, a proper planning is suggested to maximize the resource utilization at the metal finish line. Simulation results showed that productivity increases roughly three times higher than the current situation. However, the results were obtained based on several assumptions that had been made during carry out this project.